Pelatihan Penyusunan Laporan Keuangan Berbasis Aplikasi LAMIKRO pada Kelompok UMKM Kepulauan Banda Neira: Training on Preparing Financial Reports Based on the LAMIKRO Application for the MSME Group in the Banda Neira Islands - Putuhena, Hempry; Kilay, Trisye Natalia; Zalni, Zalni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The government is very optimistic about developing MSMEs by utilizing technological advances. One method taken is to use applications in preparing financial reports. The preparation of financial reports begins with identifying economic events to presenting information for economic decision making. The LAMIKRO application is based on SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) which must be met by MSMEs in preparing financial reports. With this activity, it is hoped that it can help MSME actors to be able to prepare financial reports based on the LAMIKRO application. The method used is by providing tutorials and assistance to MSME actors. This activity received a good response from partners and MSME actors so that they were very enthusiastic in participating in this activity. It is hoped that in the future it can provide an understanding of other themes that can be implemented by MSME actors in order to develop their businesses.